Evaluating dermal toxicity of the flame retardant aluminum diethylphosphinate by in silico-in vitro testing strategy - Moreira Silva, Enzo Zini; Rodrigues, Ana Carolina; Kohler, Ana Flávia; Cruz, Juliana Varella; Prado, Karin Braun; Gradia, Daniela Fiori; de Oliveira, Danielle Palma; Pestana, Cynthia Bomfim; Leme, Daniela Morais (Elsevier, 2025)
Flame retardants (FRs) are a group of chemicals used in different products to improve fire safety; however, many of them negatively impact human health, encouraging the use of safer alternatives. The aluminum diethylphosphinate (AlPi) is one of the potential alternatives to harmful FRs; however, close data gaps on human toxicity and enhanced mechanistic understanding are still needed. This study evaluated the dermal toxicity potential of AlPi using in silico models (OECD QSAR Toolbox, Toxtree) and a multi-biomarkers approach with human keratinocyte models (HaCaT cell line and reconstructed human epidermis (RHE) model). Our findings revealed no significant increases in reactive oxygen species (ROS, H2DCFDA) or pro-inflammatory cytokines (IL-6, IL-8, IL-10, IL-1β, IL12p70, TNF) in HaCaT cells exposed to AlPi at non-cytotoxic concentrations (30, 60, 120 μg/ml). This suggests that AlPi does not induce oxidative stress or inflammatory responses in the skin. Additionally, in silico predictions and in vitro assays (HaCaT - IL-6; OECD TG 439 with SkinVitro-RHE) did not classify AlPi as a skin sensitizer or skin irritant. Regarding changes in DNA, AlPi-exposed HaCaT cells did not show significant levels of γ-H2AX; however, this FR increased the level of 5-hydroxymethylcytosine (5-hmC) and TET1 expression, which is a gene involved in the regulation of the DNA methylation. In summary, most biomarker responses indicated that AlPi poses minimal toxic effects on the skin; however, further research is needed to understand better the biological consequences of its effect on DNA methylation.